Risk factors, immune response and whole‐genome sequencing of SARS‐CoV‐2 in a cruise ship outbreak in Norway. (May 2022) - Gravningen, Kirsten; Henriksen, Stian; Hungnes, Olav; Svendsen, Kristian; MacDonald, Emily; Schirmer, Henrik; Stene-Johansen, Kathrine; Simonsen, Gunnar Skov; Kacelnik, Oliver; Elstrøm, Petter; Bragstad, Karoline; Rinaldo, Christine Hanssen
Abstract: Objective: To improve understanding of SARS-CoV-2-transmission and prevention measures on cruise ships, we investigated a Norwegian cruise ship outbreak from July to August 2020 using a multidisciplinary approach after a rapid outbreak response launched by local and national health authorities. Methods: We conducted a cross-sectional study among crew members using epidemiologic data and results from SARS-CoV-2 polymerase chain reaction (PCR) of nasopharynx-oropharynx samples, antibody analyses of blood samples, and whole-genome sequencing. Results: We included 114 multinational crew members (71% participation), median age 36 years, and 69% male. The attack rate was 33%; 32 of 37 outbreak cases were seropositive 5-10 days after PCR. One PCR-negative participant was seropositive, suggesting a previous infection. Network-analysis showed clusters based on common exposures, including embarkation date, nationality, sharing a cabin with an infected cabin-mate (adjusted odds ratio [AOR] 3.27; 95% confidence interval [CI] 0.97-11.07, p = 0.057), and specific workplaces (mechanical operations: 9.17 [1.82-45.78], catering: 6.11 [1.83-20.38]). Breaches in testing, quarantine, and isolation practices before/during expeditions were reported. Whole-genome sequencing revealed lineage B.1.36, previously identified in Asia. Despite extensive sequencing, the continued transmission of B.1.36 in Norway was not detected. Conclusions: Our findings confirm the high risk of SARS-CoV-2-transmission on cruise ships related to workplace and cabin type and show that continued community transmission after the outbreak could be stopped by implementing immediate infection control measures at the final destination. Graphical abstract: Image, graphical abstract